Daya Patogenitas Cendawan Cunninghamella sp. terhadap Rayap Tanah Coptotermes sp. Pathogenic Ability of Cunninghamella sp. against Subterranean Termites Coptotermes sp - Titik Kartika; Suciatmih Suciatmih; Didi Tarmadi; Ikhsan Guswenrivo; Arief Heru Prianto; Sulaeman Yusuf (Masyarakat Peneliti Kayu Indonesia, 2006)
Termites are the major agent in wood biodeterioration, particularly in building materials, thus its existence in wood become trouble. Chemical insecticides are widely used to prevent the lost from termites attack. The use of chemical insecticides, however, do not recomended as it may cause risk to human health, environment, and may also harm to the non-target organisms and lead to the development of pest resistance. For that reason, these situations encourage many scientists to develop and evaluate various prospective biological control of termites. One of them is utilization of entomopathogenic fungi to suppress termite population.The object of this research is learning pathogenic ability of Cunninghamella sp. (habitually found around termites nests) in termite’s mortality. The methods of this research are fungal isolation and then pathogenic test to termites (termite’s infection). The ways of termite infection are contact and digestion. The best method is based on termite’s mortality rate after infection.The results show that Cunninghamella sp. causes termites mortality significantly than control. The higher mortality rate of termites is shown by contact infection method than digestion infection method. It might indicate that contact infection method more effective to suppress termite’s population